Comparative parasite development in African buffalo and N'Dama cattle infected with either Trypanosoma congolense or T. vivax - Olubayo, R.O.; Moloo, S.K.; Naessens, Jan (1996)
African buffalo (Syncerus caffer) and trypanotolerant N'Dama cattle were compared for their resistance to overcome Trypanosoma congolense and T. vivax infections. Several compartments from the immune system were followed during the infections and compared between the two species. Several parmaeters suggested that the buffaloes were much more resistant to trypanosomiasis than the N'Dama cattle: They had a much longer prepatent period, their parasitemia levels were lower (about 100 fold in T. congolense) and anemia, measured as a drop in PCV (packed cell volume), was either very short (T. congolense) or not present (T. vivax) in buffaloes. The N'Dama produced neutralizing antibodies before the buffalo, ruling out such antibodies as the cause of the buffalo's greater resistance to trypanosomiasis. Changes in lymphocyte populations were similar in both buffalo and N'Dama: a decrease in CD2+ T cells, but an increase in gamma/ T cells and B cells. However, neutrophils increased in buffalo, while they dropped in N'Dama, suggesting that they may play a role in the resistance of the buffalo. An unidentified leukocyte population that could not be identified by its surface phenotype, appeared in the peripheral blood of the buffalo, but not in N'Dama, around the time the PCV started to droIt is possible that these cells are immature erythroid cells produced by a more effective erythropoiesis in buffalo.